Tranexamic Acid for the Prevention and Treatment of Postpartum Hemorrhage. Issue 1 (March 2019) - Sentilhes, L.; Lasocki, S.; Ducloy-Bouthors, A.S.; Deruelle, P.; Dreyfus, M.; Perrotin, F.; Goffinet, F.; Deneux-Tharaux, C.
Abstract : ( Br J Anaesth . 2015;114:576–587) Postpartum hemorrhage (PPH) is a major cause of maternal mortality, accounting for one-quarter of all maternal deaths worldwide. Uterotonics after birth are the only intervention that has been shown to be effective for PPH prevention. Tranexamic acid (TXA), an antifibrinolytic agent, has therefore been investigated as a potentially useful complement to this for both prevention and treatment because its hypothesized mechanism of action in PPH supplements that of uterotonics and because it has been proven to reduce blood loss in elective surgery, bleeding in trauma patients, and menstrual blood loss. This review covers evidence from randomized controlled trials (RCTs) for PPH prevention after cesarean (n1/410) and vaginal (n1/42) deliveries and for PPH treatment after vaginal delivery (n1/41). It discusses TXA efficacy and side effects overall and in relation to the various doses studied for both indications.